Evaluation of occlusal bite force distribution by T-Scan in orthodontic patients with different occlusal characteristics: a cross sectional-observational study - Huda Abutayyem; Lovely M Annamma; Vijay B Desai; Mohammad Khursheed Alam (BMC, 2023)
Abstract Background The aim of orthodontic treatment, apart from esthetic and functional corrections, is uniform force distribution. Hence Occlusal analysis using a T scan gives scope for a precisely targeted treatment plan. The T-scan evaluation of occlusal force, time, and location of contacts from initial occlusal contact to maximum intercuspation enables the orthodontist to sequentially balance the occlusal forces on the right and left sides through specific treatment plan options. Objective The current study aimed to determine the force distribution in the different individuals by using a T-Scan as well as the net discrepancies of forces generated at a maximum intercuspation position in the first molar region between the left and right sides of the mouth. Methods This is a descriptive-correlational study that was carried out in Ras Al Khaimah College of Dental Sciences clinics and Ajman University clinics from January 2020 to September 2022 by using the convenience sampling technique. The T-scan III Novus was employed in this investigation to record multi-bite scans for several patients. T-scan was utilised to examine various malocclusions. Results The present study consisted of 158 participants. Analysis of Variance (ANOVA) showed that there is a statistically significant difference in the percentage of force between the three types of malocclusions (I, II, and III) on the right molar side (B-16 and B-46) (p < 0.05). Moreover, the overall discrepancy showed a statistically significant difference in the three types of malocclusion classifications (p < 0.05). On the other hand, there was no statistically significant difference in the percentage of force between B-26 and B-36 (p > 0.05). Post hoc analysis showed a statistically significant difference in the percentage of force between malocclusion classes I and III on the right molar, with a mean difference of 4.11190 (p < 0.05). Similarly, there was a statistically significant difference in B-46 between Malocclusion Classes I and II, 4.01806 (p < 0.05). Additionally, post hoc analysis showed a statistically significant difference between malocclusion classes I and III, with a mean difference of -4.79841 (p < 0.05) on the right molar. Conclusion The T-Scan is a useful tool for assessing occlusal discrepancies and can be helpful during treatment planning and follow-up, especially for orthognathic surgery patients. A T-scan could be used in orthodontic therapy in a simple and efficient way. Also, it turned out to be a useful tool for diagnosing problems and gave us new information about how therapies work. In this study, T-Scan showed that it can measure occlusal forces in timing in an objective, accurate, and repeated manner. The current study found that T-Scan was better able to report the difference in the percentage of force on the right molar side than on the left side.